Infant feeding practices at routine PMTCT sites, South Africa: results of a prospective observational study amongst HIV exposed and unexposed infants - birth to 9 months - Goga Ameena E; Doherty Tanya; Jackson Debra J; Sanders David; Colvin Mark; Chopra Mickey; Kuhn Louise (BMC, 2012)
Abstract Background We sought to investigate infant feeding practices amongst HIV-positive and -negative mothers (0-9 months postpartum) and describe the association between infant feeding practices and HIV-free survival. Methods Infant feeding data from a prospective observational cohort study conducted at three (of 18) purposively-selected routine South African PMTCT sites, 2002-2003, were analysed. Infant feeding data (previous 4 days) were gathered during home visits at 3, 5, 7, 9, 12, 16, 20, 24, 28, 32 and 36 weeks postpartum. Four feeding groups were of interest, namely exclusive breastfeeding, mixed breastfeeding, exclusive formula feeding and mixed formula feeding. Cox proportional hazards models were fitted to investigate associations between feeding practices (0-12 weeks) and infant HIV-free survival. Results Six hundred and sixty five HIV-positive and 218 HIV-negative women were recruited antenatally and followed-up until 36 weeks postpartum. Amongst mothers who breastfed between 3 weeks and 6 months postpartum, significantly more HIV-positive mothers practiced exclusive breastfeeding compared with HIV-negative: at 3 weeks 130 (42%) versus 33 (17%) (p < 0.01); this dropped to 17 (11%) versus 1 (0.7%) by four months postpartum. Amongst mothers practicing mixed breastfeeding between 3 weeks and 6 months postpartum, significantly more HIV-negative mothers used commercially available breast milk substitutes (p < 0.02) and use of these peaked between 9 and 12 weeks. The probability of postnatal HIV or death was lowest amongst infants living in the best resourced site who avoided breastfeeding, and highest amongst infants living in the rural site who stopped breastfeeding early (mean and standard deviations: 10.7% ± 3% versus 46% ± 11%). Conclusions Although feeding practices were poor amongst HIV-positive and -negative mothers, HIV-positive mothers undertake safer infant feeding practices, possibly due to counseling provided through the routine PMTCT programme. The data on differences in infant outcome by feeding practice and site validate the WHO 2009 recommendations that site differences should guide feeding practices amongst HIV-positive mothers. Strong interventions are needed to promote exclusive breastfeeding (to 6 months) with continued breastfeeding thereafter amongst HIV-negative motherswho are still the majority of mothers even in high HIV prevalence setting like South Africa.